Murder as Importation: An Empirical Study of the Continuity of Homicide Offending From Community to Confinement. Issue 4 (November 2020) - DeLisi, Matt; Butler, H. Daniel
Prison murder is the most severe form of institutional violence but its exceedingly low prevalence has limited prior research. Recent studies of prison murders make clear that serious, violent, and chronic career criminals are most likely to perpetrate inmate murders with equivocal evidence of the role of prior homicide offending on prison murder. Using retrospective administrative data from 1, 005 prisoners selected from the southwestern United States, the current study examined whether homicide offending in the community is itself an importation factor that is useful for understanding prison murder and thus can be used to understand continuity in homicidal offending from the community to confinement context. Rare events logistic regression models found that individuals sentenced for first-degree murder are more likely to perpetrate prison murder. A separate rare events logistic regression model with any type of homicide commitment offense as a predictor provided similar findings suggesting these effects are robust to model specification. Given its gravity and fundamental threat to prison safety and security, we encourage data collection and additional research on prison murder and the inmates that perpetrate it.